Analisis Linguistik Hadis Awal Ramadhan: Komparasi Fa In Gumma dan Fa In Gubiya serta Implikasi Hisab-Istikmal: Linguistic Analysis of Hadith on the Beginning of Ramadan: A Comparison of Fa in Gumma and Fa in Gubiya and Its Implications for Hisab-Istikmal - Arifuddin Ahmad; Zubair; Abd. Bashir Fatmal (Institut Daarul Qur'an Jakarta, Indonesia, 2026)
The determination of the beginning of Ramadan remains a central debate in Islamic studies, particularly regarding the methods of rukyat (crescent sighting), hisab (astronomical calculation), and istikmal (completion of thirty days). This article analyzes two variant hadith formulations concerning the non-visibility of the crescent: fa in gumma and fa in gubiya, and examines their linguistic implications for the legal construction of determining the lunar month. Using a qualitative approach grounded in semantic-lexical analysis and usul al-fiqh, the study focuses on the commands faqdurū lah and fa akmilū. The findings show that fa in gumma (when the crescent is obscured by external factors) is followed by faqdurū lah, which semantically denotes measurement and precise determination, thus supporting the legitimacy of astronomical calculation (hisab). Conversely, fa in gubiya reflects epistemic limitation, making istikmal a valid and practical legal solution. This study argues that hisab and istikmal are not contradictory but represent complementary legal mechanisms, adaptable to differing epistemic capacities and guided by the principle of maslahah.